The EU Experience in Financial Services Liberalization: A Model for GATS Negotiations? - Paula Bongini (SUERF - The European Money and Finance Forum, 2003)
The investigation of the sequencing of liberalization in the EU financial services industry is the primary object of this study. The relevance of the EU model for financial liberalization is threefold. First, the EU route towards liberalization in financial services could be regarded as a blueprint for opening up markets worldwide, especially in the context of multilateral liberalization within the WTO framework. Second, the EU model calls for an investigation of the degree of compatibility between regional agreements and multilateral commitments. Third, the EU regional experience raises the question of the extent to which it can be transferred in different settings and used elsewhere without the supranational legislative, judicial and administrative structure of the European Community. I argue that the intra-EU approach - minimum harmonization, mutual recognition and home country control - has a potential for widespread validity.
Keywords: G21; G28; F36; 330; Banks; Bank regulation; Financial Liberalization; Finanzmarktregulierung; Bankenaufsicht; Finanzdienstleistung; Bank; EU-Binnenmarkt; GATS; EU-Staaten